To Evaluate the Role of Serum Sialic Acid as Non-Invasive Bio-marker of Leukoplakia and Oral Cancer - Tagar, Muhammad Rafique; Khuhawar, Saleem Raza; Shah, Yousif Ali; Shaikh, Mushtaque Ahmed; Shaikh, Ashfaque Ahmed; Ghanghro, Allah Bux; Hafeez, Muhammad Abdul (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To evaluate the role of serum sialic acid as a non-invasive biomarker of Leukoplakia and oral cancer. METHODOLOGY: This comparative cross-sectional study was conducted from December 2017 to November 2019 at the Institute of Biochemistry and Tertiary care hospital, Larkana. The 34 diagnosed cases of oral Leukoplakia and Erythroplakia were 20 to 72 years age. The controls with history of using tobacco, areca nut, alcohol, corticosteroid drugs and systemic diseases were excluded from this study. The dysplasia was graded histopathologically as mild, moderate and severe. The Blood samples were collected and centrifuged at 3000 rpm for 15 minutes; then, serum was separated and Sialic Acid was analyzed spectrophotometrically. Finally, Statistical analysis was done by SPSS version 20 and results were expressed with mean and standard deviation. RESULTS: Out of 34 cases and controls15 (44.1%) were male, and 19(55.9%) were female. Their ages were from 20 to 72 years, and the mean age was 47.47±17.97. The typical sites of lesion were buccal mucosa 35.3%, tongue 26.5%, right cheek 14.70%, left cheek 8.8%, Juxta mandibular area 8.8% and lip 2.9%, respectively. Clinically Oral Leukoplakia was 58.8% and Erythroplakia 29.4%. The Sialic Acid levels were 78.7±16.6 mg/dl in Leukoplakia, 105.4±22mg/dl in Erythroplakia and was 60.2±4 mg/dl in controls. The serum sialic acid levels were increased in case group as compared to control group in both genders, with significant p-value 0.001. CONCLUSION: The Sialic Acid levels were significantly increased in cases of Oral Leukoplakia and Erythroplakia as compared to healthy controls. KEY WORDS: Sialic Acid, Oral Leukoplakia, Erythroplakia, Buccal mucosa, Juxta mandibular